Molecular Characterization of Predominant Serotypes, Drug Resistance, and Virulence Genes of Streptococcus pneumoniae Isolates From East China - Huang, Li-Dan; Yang, Mei-Juan; Huang, Yan-Ying; Jiang, Ke-Yi; Yan, Jie; Sun, Ai-Hua (Frontiers in Microbiology, 2022)
Streptococcus pneumoniae is a common diplococcal pathogen in the world. Characterization of the predominant serotypes, drug resistance and virulence genes in S. pneumoniae isolates prevailing in different areas and countries are clinically important for choice of antibiotics and improvement of vaccines. In the present study, pneumonia (78.7%) and meningitis (37.0%) were found as the predominant diseases in the 282 child and 27 adult S. pneumoniae-infected patients (p<0.05) from seven hospitals in different areas of East China, respectively. 90.3% in the total of 309 pneumococcal isolates could be classified into 15 serotypes by PCRs, in which the 19F (27.2%) and then the 6A/B (19.1%) acted as the predominant serotypes (p<0.05). However, the 15A and 15B/C serotypes with a total positive rate of 10.4% are not included in the 13-valent pneumococcal conjugate vaccine used in China. The E-test confirmed that the 309 pneumococcal isolates displayed >95% susceptibility rates to moxifloxacin and levofloxacin as well as 18.4%, 85.8% and 81.6% susceptibility rates to penicillin, cefotaxime and imipenem, respectively, but a significant correlation between the prevalence of predominant serotypes and their penicillin resistance was found (p<0.05). In particular, all the pneumococcal isolates showed >95% resistance rates to erythromycin and azithromycin. In the nine detected virulence genes, lytA, ply, hysA and nanA acted as the main virulence genes with >95%-100% positive rates in the 309 pneumococcal isolates while pavA and psaA genes displayed significant correlations with pneumococcal bacteremia and meningitis (p<0.05). All the data suggested that the predominant serotypes, drug resistance and virulence genes in the S. pneumoniae isolates prevailing in East China display a regional diversity compared to those from other areas of China and adjacent countries.